Research Status and Trends in the Flipped Classroom Model for Learning with Technology: A Systematic Review of Peer-reviewed Empirical Studies Published in Different Journals up to 2022 - Alharbi, Hanaa Eid (Journal of Educational and Psychological Sciences, 2023)
The current study aims to investigate research trends in the flipped classroom model (FCM). To achieve this, 823 peer-reviewed empirical studies published in different journals up to 2022 were selected and systematically reviewed. According to the data, FCM research receives more scholarly attention each year. The trend that was found in FCM research is that participants are generally chosen from the undergraduate level, and the majority of participants were found to be students. Furthermore, FCM researchers have applied various research methods during the past years; however, they have shown a preference for the quantitative design. The findings of this review show that research on the FCM is more commonly conducted in the fields of medical and health sciences and language than in other disciplines. These findings are expected to provide a better understanding of the status and trends associated with the FCM and help to visualize future practice and research directions.
Keywords: Educational technology; Flipped classroom model; Flipped learning; Teaching/learning strategies; Systematic reviews